2012
DOI: 10.1007/s00701-011-1265-1
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord herniation: Management and outcome in a series of 12 consecutives patients and review of the literature

Abstract: The authors present one of the largest studies to date regarding patients with spinal cord herniation and emphasize that the possibility of this condition must be kept in mind when addressing all patients with progressive myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…The most frequent misinterpretation is as a dorsal arachnoid cyst[145678101112131415161718192021232425] previously reported as a false diagnosis in around 45% of cases,[7980] but it has been reported that an associated dorsal arachnoid cyst is potentially present in 20-25% of patients with ISCH. [7980] Other misdiagnoses include thoracic disc herniation,[1213] transverse myelitis,[914] arachnoiditis,[4] intradural mass,[9] and extradural compressive lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent misinterpretation is as a dorsal arachnoid cyst[145678101112131415161718192021232425] previously reported as a false diagnosis in around 45% of cases,[7980] but it has been reported that an associated dorsal arachnoid cyst is potentially present in 20-25% of patients with ISCH. [7980] Other misdiagnoses include thoracic disc herniation,[1213] transverse myelitis,[914] arachnoiditis,[4] intradural mass,[9] and extradural compressive lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Prada et al . [17] reported a series of 12 ISCH cases, with 50% of patients showing improved symptomatology after surgery, and the others remained free from symptom progression. Another series of 12 patients, with a mean follow-up period of 74 months, described postoperative improvement in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…7 Prada et al described a series of 12 patients in which all patients underwent surgical correction via a posterior approach, with reduction of the herniated spinal cord, positioning of a muscular autograft to fill the anterior cavity, and closure of the dural defect with an artificial dural patch. 5 In this case, a possible reason why the initial dural repair failed in the initial vertebrectomy when the durotomy occurred was that the dural substitute was placed over the durotomy, i.e., on the outside of the thecal sac. This placement allows for pulsation of CSF or cord to push the patch away from the defect, and increases the risk of CSF leak and/or cord herniation (rarely).…”
Section: Discussionmentioning
confidence: 97%
“…[2][3][4] A well-defined set of MR imaging diagnostic criteria has been established for STSCH 2,[4][5][6] ; however, little has been said about postoperative MR imaging of changes in the spinal cord and adjacent structures. Less than half of the cases reported in the literature have described postoperative MR imaging features after reduction of spinal cord herniation 1,4,[7][8][9][10] ; none provided descriptions of a rational analysis; and in cases of complications, few have performed time-related assessments of the findings. The lack of a thorough knowledge of postoperative MR imaging findings and their evolution with time can lead to misinterpretations of normal postoperative changes and oversight of complications.…”
mentioning
confidence: 99%